High betatrophin in coronary patients protects from cardiovascular events. (January 2020) - Leiherer, Andreas; Ebner, Janine; Muendlein, Axel; Brandtner, Eva M.; Zach, Christina; Geiger, Kathrin; Fraunberger, Peter; Drexel, Heinz
Abstract: Background and aims: Betatrophin, also known as angiopoietin-like protein 8 (ANGPTL8) or lipasin, is a nutritionally-regulated mammalian-specific protein secreted by the liver and adipose tissue. Many conflicting data exist with respect to its association with type 2 diabetes mellitus (T2DM), insulin resistance, and lipid markers, but no data are available on its association with cardiovascular risk. Methods: We measured betatrophin in 553 coronary patients undergoing coronary angiography for the evaluation of established or suspected stable coronary artery disease (CAD) and prospectively recorded cardiovascular events during a follow-up of up to 8 years. Results: During follow-up, 201 patients suffered a cardiovascular event and 64 died from cardiovascular causes. High betatrophin (upper tertile) was significantly and inversely associated with cardiovascular events both univariately (HR = 0.64 [95%CI 0.47–0.87], p = 0.004) and after full adjustment including the status of CAD and T2DM (adj. HR = 0.55 [95%CI 0.40–0.76], p < 0.001). The inclusion of betatrophin into a basic prediction model for the cardiovascular event risk significantly improved the model performance (NRI = 0.728, p < 0.001). Conclusions: This study is the first to show that betatrophin predicts cardiovascular events independently of conventional risk factors including the presence of CAD and T2DM. Graphical abstract: Image 1 Highlights: Betatrophin was measured in 553 coronary patients. Cardiovascular events were followed for up to 8 years. High betatrophin protects from cardiovascular events and death. Betatrophin was not associated with the presence or extent of atherosclerosis.